Human Development and Economic Growth in Unequal Contexts: A comparative Analysis of Greece and Georgia - Argiro K. Moudatsou; Tsiklashvili, Natela; Tsetskhladze, Murman; Poladashvili, Tamari; Turmanidze, Tamila (European Journal of Sustainable Development, 2025)
This study examines the relationship between human development and economic growth in two small economies at different stages of development—Greece, an EU member, and Georgia, a transitioning post-Soviet state. Using an Autoregressive Distributed Lag (ARDL) model over the period 1990–2022, the analysis evaluates the role of the Human Development Index (HDI) alongside key macroeconomic variables such as capital formation, government expenditure, trade openness, and population growth. While numerous studies explore the HDI-growth nexus, few focus on small or transitioning economies, and even fewer offer comparative insights between countries embedded in the EU institutional framework and those navigating post-transition reforms. Our findings reveal that HDI significantly influences economic growth in both contexts, but the nature of the relationship diverges: Georgia shows a delayed, linear impact of HDI on growth, whereas in Greece, a non-linear relationship emerges, where higher levels of human development yield compounding economic benefits. Capital investment and fiscal policy also display different dynamics—inefficient and contractionary in Georgia, but more growth-enhancing in Greece. These insights are particularly relevant amid ongoing discussions about EU cohesion, sustainable convergence, and the development trajectories of post-Soviet economies. The study underscores the importance of tailored policy strategies: Georgia must focus on institutional reform, investment efficiency, and public sector effectiveness, while Greece needs to leverage human capital to sustain long-term growth. By comparing two structurally distinct economies, this research contributes to the literature on development heterogeneity and offers actionable guidance for policymakers in similar national contexts. Keywords: human development index, economic growth, ARDL Model, Greece, Georgia, transition economies, EU Policy